Organic Electronics: 1 GHz Pentacene Diode Rectifiers Enabled by Controlled Film Deposition on SAM‐Treated Au Anodes (Adv. Electron. Mater. 2/2016). (February 2016) - Kang, Chan‐mo; Wade, Jessica; Yun, Sumin; Lim, Jaehoon; Cho, Hyunduck; Roh, Jeongkyun; Lee, Hyunkoo; Nam, Sangwook; Bradley, Donal D. C.; Kim, Ji‐Seon; Lee, Changhee
Abstract : A gigahertz‐operable pentacene rectifier enabled by controlled film formation using a self‐assembled monolayer (SAM) is demonstrated by Kang et al. in article number 1500282. Pentacene deposited on SAM‐treated Au forms an ordered structure, thereby exhibiting much improved electrical characteristics, in contrast with a disordered pentacene structure on bare Au. Moreover, SAM treatment lowers the charge injection barrier, which further improves the device performance.